Normal Toeplitz Operators on the Bergman Space - Sumin Kim; Jongrak Lee (Mathematics, 2020)
In this paper, we give a characterization of normality of Toeplitz operator <semantics>Tφ</semantics> on the Bergman space <semantics>A2(D)</semantics>. First, we state basic properties for Toeplitz operator <semantics>Tφ</semantics> on <semantics>A2(D)</semantics>. Next, we consider the normal Toeplitz operator <semantics>Tφ</semantics> on <semantics>A2(D)</semantics> in terms of harmonic symbols <semantics>φ</semantics>. Finally, we characterize the normal Toeplitz operators <semantics>Tφ</semantics> with non-harmonic symbols acting on <semantics>A2(D)</semantics>.